User Experience Practices in Software Startups: A Systematic Mapping Study. (28th April 2022) - Guerino, Guilherme Corredato; de Assumpção, Marcos; José da Silva, Thiago; Hokkanen, Laura; Balancieri, Renato; Lapasini Leal, Gislaine Camila
Abstract : Software startups work in an uncertain environment with limited resources. Thus, user experience (UX) practices can help startups in their product development process and provide greater chances of survival for these companies. It is necessary to know what UX practices software startups have used, how they are using them, and their effects on the organization. Therefore, this paper aims to present a systematic mapping study (SMS) conducted through search engines and snowballing to identify UX practices used in software startups. The papers' analysis identified thirty-six UX practices used by startups for product validation, design, and evaluation. However, the most emergent result extracted from the analysis was that only two of these practices were specified for software startups; in contrast, the others could be applied to various company types. In addition, several functions and ways of generating customer value through UX were identified.